Retrospective Study Comparing Clinical Outcomes of Fixed Dental Prostheses in Matched Groups of Bruxer and Nonbruxer Patients - Mohammed Hawthan; Bruno R. Chrcanovic; Christel Larsson (Hindawi Limited, 2022)
Background. Tooth-supported fixed dental prosthesis (FDP) is one of the most reliable treatment options to replace missing teeth. The longevity of the treatment could, however, be affected by several general and local factors, especially bruxism. Objective. To investigate the influence of bruxism on the long-term survival of tooth-supported FDPs in bruxers compared to a matched group of nonbruxers, taking several clinical variables into account. Materials and Methods. The present retrospective cohort study was based on records of patients treated with 3-7-unit tooth-supported FDPs with a minimum follow-up time of 6 months after prosthesis delivery. The criteria for the diagnosis of "possible" and "probable" sleep or awake bruxism were used. A matched group of nonbruxers was selected on the basis of similarities in four factors, patients' gender and age, number of prosthetic units of the FDPs, and follow-up time. The paired-samples t-test or Wilcoxon signed rank test were used to compared mean values between the two groups. Contingency tables of categorical data were analyzed by McNemar's test. Results. The cohort group consisted of 62 noncantilevered FDPs in each group, followed up for a mean of 110.1 and 106.5 months (bruxers and nonbruxers, respectively). Tooth-supported FDPs in bruxers presented significantly higher failure rate than in nonbruxers (32.3% vs. 25.8%, respectively; p=0.001). Loss of retention and tooth loss were the main reasons for failures in both groups. For nonsmokers, the FDP failure rate was higher in nonbruxers. Technical and biological complications were significantly more prevalent in bruxers compared to nonbruxers. Conclusions. Bruxism is suggested to increase technical and biological complications and FDP failure.